Rationality and science : can science explain everything? - Trigg, Roger (Oxford, UK ; Cambridge, Mass., USA : Blackwell, 1993)
"Can science hope to provide a 'Theory of Everything', a final explanation of the nature of the Universe? Is science our sole source of knowledge? These questions are being increasingly asked and yet at the same time many distrust science and have become disillusioned with its effects on our world. Can science and scientific practice be justified? What are the rational foundations of science?" "Many contemporary philosophers are bewitched by the idea that there must be some neutral ground or a 'God's-eye view' to which we can appeal when we wish to justify a whole conceptual scheme. The impossibility of finding one drives many to relativism. How far can reason, and the idea of reality, be upheld in the face of this criticism?" "In this important new book, Professor Trigg faces these issues squarely and examines how far it is possible to give reasons for trusting science. In defending a realist outlook, Trigg aims to show that even physical science must be given metaphysical foundations. In so doing, he explains and evaluates the views of Rorty, Wittgenstein, Quine, Putnam, and Hawking, amongst others. The limits of science and rationality are explored and the power of human reason is in the end upheld."--Jacket.
Acknowledgements -- introduction -- 1. Science and reason -- 2. Science and pragmatism -- 3. The end of reason -- 4. Science and naturalism -- 5. A God's-eye view -- 6. Science and humanity -- 7. Science and society -- 8. Can science explain everything? -- 9. The legitimation of science -- 10. Reason and metaphysics -- References -- Index.
Cover title: Rationality & science.
Includes bibliographical references (pages 240-243) and index.
Keywords: Science -- Philosophy; Science -- Philosophy; Sciences -- Aspect social; Raison; Science -- Philosophy